DESIGN AND IMPLEMENTATION OF HYBRID STORAGE SYSTEM COMPOSED BY BATTERY AND ULTRACAPACITOR IN ELECTRIC VEHICLE - Shefali Sharad Kasawar; Prof.(Dr.)B. E. Kushare (International Journal of Innovations in Engineering Research and Technology, 2021)
he main aim of our proposed system is to improve the efficiency and stability of used converters. The control of hybrid storage systems by batteries and ultra capacitors is proposed .A voltage and current controller is used to achieve the control. Simulation is performed in MATLAB SIMULATION and the results show the relevance of our approach. So in view of practical implementation, it will be required to improve the modeling of storage elements (battery, ultra capacitors, inductors and capacitors). Moreover, the performances of our hybrid energy storage system must be subjected to a variable load.